Tumor-Stroma Interactions Alter the Sensitivity of Drug in Breast Cancer - Brancato, Virginia; Kundu, Banani; Oliveira, Joaquim Miguel; Correlo, Vitor Manuel; Reis, Rui Luis; Kundu, Subhas C. (Frontiers in Materials, 2020)
Flat cell cultures or xenografts are inadequate tools to unravel cancer complex biology. 3D in vitro tumor models garnered interest since they recapitulate better dynamic mechanisms of cancer, but a gold standard model that faithfully mimics solid cancer is not available yet. 3D breast cancer model is fabricated using freeze-dried silk fibroin scaffolds. Breast cancer cell lines (MCF-7 and MDA-MB231) are seeded with normal mammary fibroblasts onto silk fibroin scaffold (1 mm and 2 mm thick). Cells proliferation is monitored by means of Alamar blue assay. 3D breast cancer models morphology is observed by confocal microscopy. Gene expression modulation concerning extracellular matrix markers is evaluated. Further, 3D bioengineered breast cancer models are treated with doxorubicin. Silk fibroin scaffolds allow the proliferation of cancer cells and fibroblasts. Cells growth is enhanced when cancer cells and fibroblasts are seeded together. Histological staining shows 3D cell organization. MMP-1, MMP-2, MMP-3, Col-1 and Fibronectin expression is upregulated in co-culture. After doxorubicin treatment, stronger reduction in cell activity is observed in 2 mm SF scaffold in comparison to 1 mm. The 3D in vitro breast cancer model obtained can easily be scaled-up and translated to the preclinical testing of novel chemotherapeutics.